1997
DOI: 10.1172/jci119849
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive nuclear factor-kappaB-RelA activation is required for proliferation and survival of Hodgkin's disease tumor cells.

Abstract: The pathogenesis and etiology of Hodgkin's disease, a common human malignant lymphoma, is still unresolved. As a unique characteristic, we have identified constitutive activation of the transcription factor nuclear factor (NF)-kappaB p50-RelA in Hodgkin/Reed-Sternberg (H/RS) cells, which discriminates these neoplastic cells from most cell types studied to date. In contrast to other lymphoid and nonlymphoid cell lines tested, proliferation of H/RS cells depended on activated NF-kappaB. Furthermore, constitutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
508
0
10

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 718 publications
(538 citation statements)
references
References 54 publications
20
508
0
10
Order By: Relevance
“…In a previously published study on Hodgkin cells all cells contained constitutively active NF-kB and while IkBa was not analysed in L428 cells, Western blotting of extracts from KM-H2 and HDLM-2 cells indicated that immunoreactive material which comigrated with wild type IkBa was detected at a very low level (Bargou et al, 1996). Although not mentioned, these authors also detected a more slowly migrating form of IkBa which could correspond to that observed in this report.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In a previously published study on Hodgkin cells all cells contained constitutively active NF-kB and while IkBa was not analysed in L428 cells, Western blotting of extracts from KM-H2 and HDLM-2 cells indicated that immunoreactive material which comigrated with wild type IkBa was detected at a very low level (Bargou et al, 1996). Although not mentioned, these authors also detected a more slowly migrating form of IkBa which could correspond to that observed in this report.…”
Section: Discussionsupporting
confidence: 59%
“…The conclusion of this study is that constitutive activation of NF-kB observed in Hodgkin cell lines (Bargou et al, 1996;Gruss et al, 1997; this study) is a consequence of defective IkBa. In KM-H2 cells IkBa cannot be detected under normal circumstances, but an 18 kD fragment of IkBa is detected after treatment of the cells with an inhibitor of proteasomal degradation ( Figure 5).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Finally, as the transient NF-kB activation vanishes, apoptosis can be activated by p53-independent or -dependent mechanisms. In cancer cells, however, this tightly regulated scheme could be perturbed either by p53 mutations or p53 degradation or by constitutional or sustained NF-kB activation, as described in EBVtransformed B lymphocytes, in Hodgkin's disease cells or in some breast cancer cells (Bargou et al, 1997;Sovak et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The malignant cell in HL is the Hodgkin and ReedSternberg (HRS) cell that is found at a low frequency in diseased lymph nodes, where it is surrounded by reactive immune cells. Both HL primary tumor samples and HL cell lines have constitutively active p50-RELA and p50-REL complexes, and generally little or no stable IkBa protein can be detected in these cells (Bargou et al, 1996(Bargou et al, , 1997Cabannes et al, 1999).…”
Section: Multiple Familial Trichoepitheliomamentioning
confidence: 99%